Waithood, Music, Fakes, and Well-Being: Exploring the Mobile Lives of South African Township Youth Through the Mobile Diary Method - Priscilla Boshoff; Chikezie E. Uzuegbunam; Bimbo Fafowora; Nonhlanhla Ndlovu; Alette Schoon (Journalism and Media, 2025)
South Africans enjoy increasing access to digital connectivity. But little is known about the roles that mobile phones play in the everyday lives of young South Africans who live in marginalized spaces. Responding to this gap in the literature, we conducted research with a naturally occurring group of sixteen young adults, between the ages of 18 and 34, living in an under-resourced Eastern Cape township. Using the mobile diary method, we asked these young people how they use their mobiles as part of everyday sociality and to support their well-being. The article (1) reflects on the efficacy of the mobile diary method as a means of understanding our respondents’ lives and worlds; and (2) presents four themes emerging from the data generated by this method: “waithood”, “music”, “fakes”, and “wellbeing”. We conclude that the mobile diary method generates rewardingly rich data that reveal the complexity of township digitality and sociality. This texture avoids simplistic binaries and does justice to the experiences of young people in marginalized contexts.